The Merovingians - Murray, Alexander C., 1946-
1 online resource (440 pages).
Keywords: The studies collected here cover a period of about 33 years, from 1986 to 2019, and represent a sustained effort to understand the institutions of the Merovingian kingdom and its history. There has long been a predisposition to cast the Merovingian period in the dark colours of barbarism or to treat it with reference to personal relationships and archaic institutions. The present volume, instead, recognizes the Merovingian world not as an archaic, primitive intrusion on the Mediterranean civilization of the Roman Empire but simply as a participant in the wider commonwealth that remained after the dissolution of the western imperial system; in so doing, it serves to refute the scholarly tendency to primitivize Merovingian governance, its underlying institutions, and the broader culture upon which these rested. The collection is divided into four parts. Part 1 considers the question of whether Merovingian kingship should be viewed as a species of archaic, 'sacral' kingship. Part 2, on institutions, has chapters that deal with various offices (the grafio and centenarius); public institutions (especially immunity and public security); and the broader makeup of the Merovingian state system. Part 3 on charters, procedure, and law, has chapters on the profile of the charter evidence as now presented in the new MGH edition of the Merovingian diplomas and one on particular procedures before the royal tribunal, mistakenly referred to in scholarship as 'fictitious' trials; a final chapter provides a reflection on, and basic guide to, the law in general of the successor kingdoms, with an eye to the evidence of Merovingian Gaul. Part 4, a slight change of pace, deals with historiography, both the modern variety (Reinhard Wenskus) and the Merovingian (Gregory of Tours). All chapters deal extensively with the historiography of their subjects. This book will appeal to students and scholars alike interested in Early Medieval European history, Merovingian history, Early Medieval law and society, Early Medieval historiography, and the influence of Merovingian law and governance on later centuries.